Look Back to Live Ahead: Connecting the Power of Museums and Journalism for a Stronger Democracy. - Kebede-Twumasi, Laura (Public Humanities, 2025)
Museums and news organizations make up major parts of the structure that maintains an informed community essential to democracy. As resources for both of these institutions dwindle, it's more important than ever for these sectors to work together toward their common goals – not only with each other, but with their respective communities in ways that are collaborative and egalitarian. The following outlines Civil Wrongs, a program started at the University of Memphis Department of Journalism and Strategic Media in 2022, as an emerging example of how these institutions can work together and learn from each other for the sake of a more informed community. Civil Wrongs is both a journalistic project of the nonprofit Institute for Public Service Reporting, and an academic class for junior and senior college students from multiple disciplines, including journalism, history, and political science. Through narrative podcasting, the program aims to examine past cases of racial terror in the Mid-South and analyze their connection to present-day injustices. It is a break from the traditional journalistic model that focuses solely on the present with little historical context and therefore naturally creates a bridge to museums that are grounded in history education.